Urgent release of constriction band syndrome of the leg with single-stage Z-plasty procedure in neonates: A case series - Winanto, Iman Dwi; Sofyan, Jefryan; Muchtar, Muhammad Arafat; Guci, Ricovially Davya (Jurnal Prima Medika Sains, 2024)
The congenital constriction band syndrome (CCBS) is a group of fetal abnormalities with myriad of clinical presentation that is characterized by the presence of a fibrous band that encircles fetal tissues in utero. It is a rare disease with a reported incidence of 1/15,000 live births. The disease is treated with release of the constricting band with Z-plasty, where it is classically done as a two-stage procedure. Single stage z-plasty is a relatively new approach that still needs more reports regarding to its result. Our cases described successful release with a single stage Z-plasty reconstruction in the setting of an urgent surgery in neonates aged less than 48 hours.